Legal-lay communication - Heffer, Chris. (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Introduction to the language of bribery -- Bribery : a brief history and background -- The linguistic tools for dealing with bribery -- The crystal-clear bribery events of U.S. Congressmen Ozzie Myers and Richard Kelly -- The aborted bribery event of U.S. Senator Larry Pressler -- The camouflaged bribery events of Businessmen Kenneth McDonald and Milton McGregor -- The bribery event that continued after the target said "no" : the case of U.S. Senator Harrison A. Williams -- The entrapment bribery event of taxpayer Vaughn Sligh -- The business transaction event that morphed into a bribery event : the case of Texas State Legislator Billy Clayton -- The bungled rejection of a bribery event by Nevada Brothel Commissioners John Poli and John McNown -- The coded bribery event of Federal Judge Alcee Hastings -- The manipulated bribery event of Businessman Paul Manziel -- The bribery event that never happened : the case of Businessman Vernon Drabek -- The role of linguistic analysis in bribery cases -- The legal context of bribery language and law